Investigating the appearance of new psychoactive substances in South Australia using wastewater and forensic data. Issue 2 (12th September 2018) - Bade, Richard; Stockham, Peter; Painter, Ben; Celma, Alberto; Bijlsma, Lubertus; Hernandez, Felix; White, Jason M.; Gerber, Cobus
Abstract: New psychoactive substances (NPS) have increased in use and popularity worldwide. Wastewater analysis has been successfully applied to evaluate illicit drugs use within a population. However, for NPS, such an approach may be limited due to low doses of NPS combined with their ever‐changing composition and usage. The dynamic nature of the NPS market means use may be opportunistic, infrequent, and with few users. Hence, the use of complementary information sources is recommended to improve the knowledge on NPS consumption. The aim of this study was to investigate the changing landscape of NPS use on a community scale by combining wastewater analysis and forensic toxicology. Forensic analysis provided specific information on NPS prevalence in post‐mortem blood samples in Adelaide, South Australia over five years, while wastewater analysis showed community use over the same period. A qualitative liquid chromatography–‐high resolution mass spectrometry method was initially used to screen the wastewater samples. A total of 24 NPS were found: 6 in wastewater only, 13 in forensic post‐mortem toxicology samples only, and 5 in both. As these results showed the presence of NPS, a targeted method was subsequently employed to quantify levels of these NPS in wastewater. Temporal trends were found in wastewater with distinct tendencies for synthetic cathinones visible over the period studied. Abstract : The combination of wastewater analysis and forensic toxicology to investigate new psychoactive substances in Adelaide, South Australia from June 2012 to June 2017 using both qualitative and quantitative liquid chromatography–mass spectrometry methods.